Pengaruh Model Problem Based Learning Terhadap Kemampuan Pemahaman Matematis Ditinjau Dari Kemampuan Awal Matematis Siswa - Putri Wulan Clara Davita; Hepsi Nindiasari; Anwar Mutaqin (TIRTAMATH: Jurnal Penelitian dan Pengajaran Matematika, 2020)
This study aims to determine: (1) the mathematical comprehension ability of students who obtain network-based problem-based learning models is better than students who receive online learning-based scientific learning. (2) students 'mathematical comprehension abilities at high initial mathematical abilities are better than students with moderate and low initial mathematical abilities (3) students' mathematical understanding abilities who get problem-based learning models based on online learning are better than students who get scientific learning Based on network learning in terms of initial mathematical abilities (4) there is an interaction between learning models and initial mathematical abilities (high, medium, and low) on students' mathematical understanding abilities. This research is a quantitative descriptive study. The subject matter in this research is three dimensions. The subjects in this study were 28 students of class XII SMA Negeri 1 Wanasalam for the 2019/2020 academic year consisting of 15 students in the experimental class and 14 students in the control class. The data collection method in this research is the test method. The data analysis technique in this study was by looking at the test scores of mathematical comprehension abilities in terms of high, medium and low categories. The results showed that (1) the mathematical comprehension abilities of students who obtained the network-based problem-based learning model were no better than those who received network-based learning. (2) students 'mathematical comprehension abilities at high initial mathematical abilities are no better than students with moderate and low initial mathematical abilities (3) students' mathematical understanding abilities who obtain network-based problem-based learning models are no better than students who obtain scientific learning based on learning in the network in terms of initial mathematical abilities (4) there is no interaction between learning models and initial mathematical abilities (high, medium, and low) on students' mathematical understanding abilities.